Operating Cost and Revenue Budgets and Financial Performance at PT PLN (Persero) - Faulia Anggraini; Windi Triana (Institute for Law and Economics Studies, 2026)
This study examined the effect of operating cost budgets and revenue budgets on the financial performance of PT Perusahaan Listrik Negara (Persero) Unit Tanjung Tiram, Batu Bara Regency. The research addressed the problem of fluctuating financial performance, as reflected in changes in return on assets, which indicated potential inefficiencies in budget planning and control. A quantitative approach was applied using secondary financial data covering the 2019–2023 period. The analysis employed multiple linear regression to measure the partial and simultaneous effects of operating cost budgets and revenue budgets on financial performance. The data were processed using statistical analysis software. The results showed that operating cost budgets and revenue budgets simultaneously had a significant effect on financial performance. However, when tested individually, neither operating cost budgets nor revenue budgets showed a significant partial effect on return on assets. These findings indicated that financial performance was influenced by the interaction between cost management and revenue planning rather than by a single budget component in isolation. The study concluded that integrated and balanced budget management was essential for improving financial performance, particularly in state-owned enterprises operating under public service and regulatory constraints